Mechanical properties of E-glass fibre reinforced nylon 6/6 resin composites - Srivastava V.K.; Lal S. (My University, 2025)
The tensile strength, tensile modulus, compressive strength, interlaminar shear strength and residual tensile strength of E-glass fibre reinforced nylon 6/6 resin composite with the variation of fibre volume fraction are characterized. The results are in line with the required limits of theoretical values. © 1997 Chapman & Hall.